Pengaruh Model Pembelajaran Active Learning terhadap Hasil Belajar Pendidikan Agama Kristen Siswa Kelas VII SMP Negeri 3 Siborongborong Tahun Pembelajaran 2023/2024. - Aleyda Azaria Panggabean; Tahadodo Waruwu; Frainskoy Rio Naibaho; Rida Gultom; Nisma Simorangkir (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The research aims to determine how much influence the application of the Active Learning learning model has on the learning outcomes of Christian Religious Education for class VII students at SMP Negeri 3 Siborongborong Learning Year 2023/2024. The research hypothesis is that there is a positive and significant influence of the Active Learning learning model on the learning outcomes of Christian Religious Education for class VII students at SMP Negeri 3 Siborongborong for the 2023/2024 academic year. Quantitative research method using a Pre-Experimental Design approach in the form of a One Shot Case Study. The population of all class VII students at SMP Negeri 3 Siborongborong for the 2023/2024 academic year who are Protestant Christians is 109 people. The purposive sampling system was 32 people. The research instrument is a closed number and posttest. The results of data analysis obtained: a) The value of rcount=0.369>r(table(a=0.05,n=32))=0.349 and tcount=2.172 >t(table(a=0.05,dk=n -2=30))=2.042 shows that there is a positive and significant relationship between the Active Learning learning model and students' Christian Religious Education learning outcomes. b) Regression equation Ŷ = 65.81 + 0.17X. c) The determination test revealed that the magnitude of the effect was 13.6%. d) Hypothesis testing obtained Fcount=4.575 > Ftable=1.62 then H0 is rejected and Ha is accepted. The research concluded that there was a positive and significant influence between the Active Learning learning model on the learning outcomes of Christian Religious Education for class VII students at SMP Negeri 3 Siborongborong for the 2023/2024 academic year.